Practical Aspects of Chemical Engineering Selected Contributions from PAIC 2017 (Lecture Notes on Multidisciplinary Industrial Engineering,, 2018)
This book focuses on Chemical Engineering and Processing, covering interdisciplinary innovation technologies and sciences closely related to chemical engineering, such as computer image analysis, modelling and IT. The book presents interdisciplinary aspects of chemical and biochemical engineering interconnected with process system engineering, process safety and computer science.